The global technology revolution : bio/nano/materials trends and their synergies with information technology by 2015 - Antón, Philip S. (Rand MR series, 2001)
Beyond the agricultural and industrial revolutions of the past, a global technology revolution is currently changing the world. This book discusses the broad multidisciplinary and synergistic trends in this revolution, including genomics, cloning, biomedical engineering, smart materials, agile manufacturing, nanofabricated computation devices, and integrated microsystems. The revolution's effects on human health may be the most startling as breakthroughs improve both the quality and length of human life. Biotechnology will also enable us to identify, understand, manipulate, improve, and control living organisms (including ourselves). Information technology is already revolutionizing our lives, especially in the developed world, and is a major enabler of other trends. Materials technology will produce products, components, and systems that are smaller, smarter, multifunctional, environmentally compatible, more survivable, and customizable. In addition, smart materials, agile manufacturing, and nanotechnology will change the way we produce devices and improve their capabilities. The technology revolution will not be uniform in its effect across the globe but will play out differently depending on its acceptance, investment, and a variety of issues such as bioethics, privacy, economic disparity, cultural invasion, and social reactions. There will be no turning back, however, since some societies will avail themselves of the revolution, and globalization will thus change the environment in which each society lives.